Are recent trends in poverty and deprivation in Australia consistent with trickle-down effects?. (September 2022) - Saunders, Peter; Naidoo, Yuvisthi; Wong, Melissa
This article examines trends in social disadvantage in Australia over the decade to 2018 using two approaches: a monetary approach using poverty and a living standards approach using deprivation. We compare the two approaches, highlight their implications and assess whether the evidence produced by each is consistent with trickle-down effects. The estimates allow for variations in thresholds, the treatment of housing costs and relative and absolute measures. The findings indicate an overall decline in poverty that is dependent on the treatment of housing costs and a more consistent decline in deprivation but with little or no improvement for many experiencing poverty or deprivation. Poverty and deprivation among unemployed households were above those for people in other labour force states throughout the period and while these differentials have narrowed, the findings suggest that trickle-down effects did not reach many of those highly disadvantaged or are subject to long delays. JEL Codes: I32, E65, H55